Journaal van Willem Ysbrandtsz. Bontekoe - Bontekoe, Willem Ysbrandtsz. 1587-1657; Eggink, C. (Haarlem Tjeenk Willink, 1957)
Willem IJsbrantszoon Bontekoe (Hoorn, 1587-1657) was a skipper and merchant. He is known to this day for his account of a voyage to the East Indies on behalf of the Vereenigde Oostindische Compagnie.
Keywords: Vereenigde Oostindische Compagnie; 17th Century (1601-1700); Travel; Diary; Maritime transport